Dimensions of wine hotel experiences shared online. Issue 1 (2nd December 2019) - Brochado, Ana; Troilo, Mike; Rodrigues, Helena; Oliveira-Brochado, Fernando
Abstract : Purpose: The purpose of this study sought to identify the main themes linked with wine hotel experiences, based on tourists' narratives shared online, and to investigate whether these narratives vary according to traveler type. Design/methodology/approach: Content analysis was carried out on 4, 114 online reviews of 52 wine hotels located in 27 wine regions across 11 nations in both the Old and New World. Findings: The analysis of these web reviews revealed that narratives can be grouped under 11 themes organized into 7 main dimensions as follows: wine, lodging (i.e. hotel, area and room), food service (i.e. restaurant and breakfast), scenery (i.e. views and vineyards), staff, transportation and recommendation. The main narratives vary according to traveler type. Practical implications: Improving the present understanding of wine tourists' experiences should help wine hotel managers find new approaches to enhancing visitors' satisfaction. As the dimensions of wine tourism experiences shared online vary according to traveler type, wine managers can design their offer to target families, couples, friends, solo and corporate clients. Originality/value: Prior research has identified the need for market segmentation in the wine tourism industry. This research addresses this need by specifying the wine tourism experience according to traveler type. The breadth of the data, and the method of using travelers' own testimony as opposed to more common surveying are additional contributions for both academics and managers.